Can Health Care Reform End Stigma Toward Mental Illness?. Issue 2 (3rd May 2016) - Weiss, Eugenia L.; Gross, Gregory D.; Moncrief, Don
ABSTRACT: This article addresses the destigmatization of mental health through health care reform by incorporating antistigma efforts—a destaining of mental illness—through prevention and early intervention in community-based programs that would be mandated and funded through the auspices of Patient Protection and the Affordable Care Act (ACA). Mental health care policies under the ACA and the Mental Health Parity Act are briefly described, following a definition of mental health stigma and its impacts. Recommendations for statutory mandates in stigma reduction at the community and federal levels and guidelines for mental health/behavioral health providers form the article's conclusion.